PENGARUH GAYA KEMIMPINAN MANAJER DAN DISIPLIN KERJA KARYAWAN TERHADAP KUALITAS PRODUKSI PADA BOLLY BAKERY BIMA - MUH. Rifkahul Ramdani; Jaenab - Jaenab (Universitas Mahendradatta Denpasar, 2021)
The purpose of this study was to determine and analyze the significant influence of managerial leadership style and work discipline on the quality of production at Bolly Bakery Bima. The type of research used is associative, With sample of 30 respondents. The sampling technique used was saturated sampling. Distribution of questionnaires using Likert scale measurement. Methods of data analysis using validity test, reliability test, classical assumption test, multiple linear regression analysis, correlation analysis, coefficient of determination, f test, and t test. The results of the study can be concluded that the manager's leadership style and work discipline have an influence on the quality of production at Bolly Bakery Bima, where the t value of the leadership style variable is 0.402, which is smaller than the t table value of 2.055 (0.402 2.055) with a significance value of 0.691 0.05 and the work discipline variable of 0.329 is smaller than 2.055 (0.329 2.055) with a significance value of 0.745 0.05.